Application of Quizizz App Assisted by Paper Mode on Digital Student Worksheets for Learning Short Story Texts at SMAN 1 Karanganom - Ramadhani, Lulu; Huda, Miftakhul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to apply the Quizizz app assisted by paper mode on digital student worksheets for learning short story texts at SMAN 1 Karanganom. This research is included in qualitative research with a descriptive method. The data in this study is in the form of information about the prep-aration stage and the stage of implementing the Quizizz application assisted by paper mode on digital student worksheets for learning short story texts. Methodology: Data was obtained by observation and interview methods to students regard-ing the application of the Quizizz application assisted by paper mode on digi-tal student worksheets for learning short story texts sourced from learning and the application of the Quizizz app assisted by paper mode in SMA Negeri 1 Karangnom. This study uses triangulation techniques as a data va-lidity techniques and Cresswell analysis techniques as a data analysis tech-niques. Results: The results of the study found that the application of the Quizizz application assisted by paper mode on digital student worksheets can be used easily and enjoyably. Applications/Originality/Value: The application can increase students' interest and motivation in learning and competing for high scores. The compatibility of the use of the application with Indonesian language learning, especially in short story text materi-al, has a very high level so that it reaps a very good response from students. The Quizizz application is an application that is suitable for learning short story texts.